E-cadherin, N-cadherin Expression and Histologic Characterization of Canine Choroid Plexus Tumors. (July 2016) - Reginato, A.; Girolami, D.; Menchetti, L.; Foiani, G.; Mandara, M.T.
Choroid plexus tumors (CPTs) are reported with an increasing incidence in dogs, and they call for a reexamination of histologic features and criteria of classification corresponding to their biological behavior. In this study, the human World Health Organization classification was applied to 16 canine CPTs, and the expression of molecules involved in neoplastic cell adhesion (E-cadherin, N-cadherin), invasion (doublecortin), and proliferation (Ki-67) was investigated. Mitotic index was found to be the main criterion for grading CPTs. Cell density and multilayering of papillae were also statistically associated with histologic grade. Intraventricular spread and parenchymal invasion was observed for tumors showing histologic benign features. E-cadherin was expressed in all CPT grades, independent of tumor invasion. N-cadherin immunolabeling was more expressed in grade I than high-grade CPTs, whereas doublecortin expression was not detected in CPTs. An increasing proliferative activity was observed in relation with histologic grade.